Identifikasi Morfologi Berbagai Varietas Padi Ketan (Oryza sativa L. Var. Glutinosa) pada Dataran Medium - laela anjar sari; Mahayu Woro Lestari; Novi Arafita (AGRONISMA, 2021)
Glutinous rice (Oryza sativa L. Var. Glutinose) is one type of rice that grows well from thousands of types of rice in Indonesia. The advantages of glutinous rice plants over the type of rice plants in general lies in their agronomic character, where glutinous rice plants have a larger stem circle diameter, so it has the potential as a source of germplasm plasma for rice plant breeding to withstand fractures.The purpose of the research is to find out, identify and characterize the plasma nutfah glutinous rice plants in Indonesia. The study was conducted in November 2020-April 2021. The research location in Dermo Village Village Mulyoagung District Dau Malang City East Java. The research design used is a randomized group design (RAK). The treatment is 16 varieties of glutinous rice plants, repeated 3 times so that the total number of experimental units is 54 units. Each experimental unit has 16 clumps of plants. The growth and yield of sixteen varieties of glutinous rice in general can be seen from the height of the plant and the amount of grain content perrumpun. In this study, the highest average plant height was V4 (Wangkaluku) 125.68 cm, V5 (La Uma) 123.18 cm, V6 (Wa Bila) 113.45 cm, V7 (Wa Bou) 105.71 cm, V8 (Wa Gamba) 114.24 cm, and V11 (Wuluh) 127.52 cm. As for the amount of grain contents perrumpun that has the largest number of seeds in V1 (Lokbon 1) 2502.84, V3 (Lokbon 3) 2060.10, V9 (Local Kediri) 1884.4, V12 (Princess Payaman 20 White) 1757.63, and V15 (Local Subang) 1847.96. The results showed that the morphological characteristics of sixteen varieties had varying results. On average stem color has color (green, light green, yellowish green, yellowish yellow, greenish yellow, purple tinge), average leaf color has color (green, light green, dark green), the color of the tongue and ears of the average leaf has a color (white and a tinge of purple), the average leaf neck color has a color (white), the average grain type has a size (medium, long, short), the average grain shape has a shape (medium slim, Slender round, large round, medium round), average grain color has color (brown, straw yellow, golden yellow), the average rice color has a color (black, white, red), and on the surface of the leaves and the position of the leaves sixteen varieties of glutinous rice on average have a rough surface and upright leaf position.